The Significance and representation of aesthetic among users in residential facades design: The case of the facades of self-build houses in the city of Biskra - Belarbi, Samia; Madhoui, Meriem; Belakehal, Azeddine (Technium Social Sciences Journal, 2023)
Facades are perceived as such a body shape in their urban surrounding, their beauty and significance are felt through the impact we feel towards their representativity and shape’s features. The aesthetic of the buildings’ facades has been a subject study for a set of researchers that tried to adjust the significance of expressions that deal with an aesthetic concept that is characterized by subjectivity. This is by identifying the physical properties of the interface that are most affecting the behavior of the recipient by acceptance, in order to rely on them objectively during the design process. How can we define then the aesthetic meanings and perceptions of buildings’ facades and their components among their users, especially in self-construction housing neighborhoods? Considering them as users, creators and they helped the architects in their design. Its own aesthetics is the reflection of a certain socio-cultural level, besides a certain knowledge and experience that are responsible for the construction of a popular building which is the result of the awareness (EGO). for that reason, this essay tends to shed the light on the social representation of certain buildings’ facades users, built as a self-construction model in Beni Morah (I) in Biskra (the case study), on the meaning of a beautiful facade, and its components’ significance. To make this proposition come true, we focused on analyzing social imagination methodology as an objective approach by making a list of ten expressions that are meaningful on three sides: physical indication (clear model, all its components are complete, more sophisticated), moral indication (social class, ego, more diversified and coherent, more balanced and an innovating element), pragmatic (protection and convenience). To monitor the content of the studied social perception structure a questionnaire was distributed to a sample consisting of 30 users where the degrees of approval of these statements were structured on the basis of a structural model that allows them to be classified and to determine the relationships between them and the degrees of their correlation at the same time. By using data (Dendrograms) that provided an automatic statistical computing system which allows the explanation of the general considerations that rely on the sample’s perception of the buildings concerned with the study. The results showed that the classification of the meaning relies mainly on instinctive perception (diversity – harmony, totality), and secondarily on socio-cultural considerations (Ego, social class, more sophisticated and innovated). And less importantly the scientific knowledge of the architecture (a clear model, well-balanced, convenient- protection) shows that this aesthetic side is proper to a popular building but nothing more.